The transition from Oshikwanyama to English as a medium of instruction: a case study of a rural Namibian school - Shilongo, Teressia N (Rhodes University, Faculty of Education, Department of Education, 2007)
The study investigates how rural Grade 4 teachers and learners experience the transition from Oshikwanyama to English as a medium of instruction. The study was conducted at a rural school in Oshana region in northern Namibia. The research site and participants were purposefully selected. Grade 4 teachers and learners were interviewed and observed. Relevant documents were also analyzed. The purpose was to understand participants' experiences, perceptions and practices in relation to their experience of the transition to English medium instruction. The study revealed out that both Grade 4 teachers and learners are struggling to teach and learn through the medium of English. This was borne out by participants' responses, classroom practices and document analysis, especially learners' oral presentation and written work. The conclusion is drawn that limitations in English proficiency overshadow the good intentions of the curriculum. This was evident in the fact that Grade 4 learners at a selected school found it difficult to cope with the demands of the curriculum. In addition, most of the learners have poor literacy skills even in their mother tongue, Oshikwanyama. In the linguistic sense, proficiency in the first language can pave the way for second language to flourish. If the reverse is the case then the learner might find it difficult to acquire linguistic skills in the second language. The study concludes that for the sake of effective learning, an intervention on professional development needs to be in place. This might help rural lower primary teachers to upgrade their existing skills particularly in terms of the English language proficiency as well as how to prepare learners for the transition to English.
Keywords: Education -- Namibia; Kuanyama language -- Study and teaching -- Namibia; English language -- Study and teaching -- Namibia; Language and education -- Namibia; Rural schools -- Namibia